Gordon, J. (2012). Plato’s Erotic World: From Cosmic Origins to Human Death, Cambridge, Cambridge University Press. - Riegel, Nicholas (Revista Archai, 2015)
GORDON, J. (2012). Plato’s Erotic World: From Cosmic Origins to Human Death, Cambridge, Cambridge University Press.